Preparation method of lithium squarate nanosheet, lithium squarate nanosheet prepared by preparation method and application of lithium squarate nanosheet

By preparing ultra -thin -square lithium nano tablets through solvents thermal synthesis, traditional lithium -ion batteries have the lack of irreversible lithium loss and high energy density, significantly increased the battery filling rate and energy density, extending the battery's cycle life span Essence

CN119350147AActive Publication Date: 2025-01-24DAGAO IND TECH RES INST (GUANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411478802.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have shortcomings in irreversible lithium loss and high energy density. The thickness and structure of micron-scale lithium metered acid limit their conductivity and the diffusion speed of lithium ions, affecting the battery's charge and discharge rate, cycle stability and life.

Method used

Ultrathin lithium squarate nanosheets are prepared through solvothermal synthesis. The thickness can be reduced to about 5nm, which improves the diffusion speed of lithium ions.

Benefits of technology

It significantly increased the battery charging and discharge rate, increased the energy density and cycle life of the battery, reduced the lithium power level of the material, increased the surface area of ​​the material, provided more contact area and active sites, good stability Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350147A_ABST
    Figure CN119350147A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium squarate nanosheet, the lithium squarate nanosheet prepared by the preparation method and application of the lithium squarate nanosheet. The preparation method of the lithium squarate nanosheet comprises the following steps: mixing squaric acid, a lithium source and a template regulator in alcohol, and performing solvothermal reaction to obtain the lithium squarate nanosheet. According to the method, squaric acid and a lithium source are taken as raw materials, alcohol is taken as a medium, and the ultrathin two-dimensional squaric acid lithium nanosheet is successfully synthesized through a solvothermal method under the assistance of a template regulator. The preparation method disclosed by the invention is simple, strong in usability, cheap and easily available in raw materials, energy-saving and environment-friendly, and beneficial to large-scale industrial production, and has remarkable economic and social benefits. The prepared ultrathin two-dimensional lithium squarate nanosheet is thin, has a large specific surface area, is low in lithium removal potential and has efficient lithium supplement performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a method for preparing a lithium squarate nanosheet, a lithium squarate nanosheet prepared thereby, and applications thereof. Background Art

[0002] In the field of modern battery technology, lithium-ion batteries have become the preferred energy storage solution due to their high energy density, long cycle life and low self-discharge rate. However, with the continuous improvement of battery performance requirements, traditional lithium-ion batteries have shown shortcomings in some aspects, especially in irreversible lithium loss and high energy density. In order to solve these problems, researchers have been exploring new materials and technologies, among which the development and application of lithium supplements has become an attractive research direction.

[0003] Lithium supplements are commonly used materials for replenishing lithium ions in traditional lithium-ion batteries, and they play a vital role in the battery charging and discharging process. Lithium squarate, as a known positive electrode lithium supplement material, has a higher specific capacity than traditional positive electrode materials and is suitable as a lithium supplement to compensate for the irreversible loss of lithium ions and improve energy density. However, the thickness and structure of micron-scale lithium squarate often limit its conductivity and the diffusion rate of lithium ions, resulting in limited battery charging and discharging rates, and may affect the battery's cycle stability and life. To overcome these challenges, researchers have explored different preparation methods to improve the performance of lithium squarate.

[0004] CN113443973A discloses a lithium squarate and its preparation method and application, wherein the lithium squarate is prepared by treating an aqueous solution by freeze drying, and its delithiation potential is reduced from 4.2 to 3.8 V by reducing the size of the lithium squarate to nanometer level (50-100 nm). However, the high cost and disadvantage of mass production of this method limit its application in large-scale production.

[0005] CN118324621A discloses a lithium squarate and its preparation method and application. The method comprises the following steps: precursor distribution modification-mixed heat treatment and then hydrothermal treatment to obtain a saturated lithium squarate solution, which is then hydrothermally treated and recrystallized to obtain lithium squarate. The lithium squarate is added as a lithium supplement to improve the capacity of the battery. However, the method has many operation steps and water is used as a solvent, which inevitably leads to the aggregation and accumulation of lithium squarate in the subsequent drying process.

[0006] CN115417754A discloses a nano-lithium squarate and its preparation method, positive electrode sheet and lithium battery. The recrystallization method is used to prepare lithium squarate with an average particle size of 100 to 500 nm, which is applied to the lithium iron phosphate system to effectively improve the first charge capacity and coulomb efficiency of the full battery, reduce the first irreversible lithium loss, and improve the cycle and energy density. Although this method shows potential in improving battery performance, the operation is relatively cumbersome, the equipment requirements are high, and there are challenges in large-scale production.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a squarate lithium nanosheet, a squarate lithium nanosheet prepared thereby and an application thereof. The method for preparing a squarate lithium nanosheet of the present invention prepares ultra-thin squarate lithium nanosheets by a solvent thermal synthesis method, has a simple preparation process, high stability, easy operation, and low cost, and the thickness of the prepared squarate lithium nanosheet can be reduced to about 5nm, and the ultra-thin structural design enables lithium ions to diffuse faster in the electrode material, thereby significantly improving the charge and discharge rate of the battery.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, the present invention provides a method for preparing a lithium squarate nanosheet, the method for preparing the lithium squarate nanosheet comprising:

[0011] Squarate, a lithium source and a template regulator are mixed in alcohol and then subjected to a solvent thermal reaction to obtain squarate lithium nanosheets.

[0012] Preferably, the molar ratio of the squaric acid to the lithium in the lithium source is 1:(2.0-2.4).

[0013] Preferably, the lithium source includes any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium bicarbonate or lithium acetate, or a combination of at least two thereof.

[0014] Preferably, the added amount of the template regulator accounts for 0.1-5.0% of the total mass of the squaric acid and the lithium source.

[0015] Preferably, the template regulator includes any one or a combination of at least two of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecylsulfonate, oleic acid or polyethylene glycol.

[0016] Preferably, the added amount of the alcohol is 1 to 5 times the total mass of the squaric acid and the lithium source.

[0017] Preferably, the alcohol is selected from any one or a combination of at least two of ethanol, ethylene glycol, glycerol, pentaerythritol, trimethylolethane, xylitol or sorbitol.

[0018] Preferably, the mixing is performed under stirring conditions, the stirring speed is 200 to 1500 rpm, the stirring temperature is 5 to 80° C., and the stirring time is 0.5 to 2 h.

[0019] Preferably, the temperature of the solvent thermal reaction is 100 to 160° C., and the time of the solvent thermal reaction is 4 to 12 hours.

[0020] In a second aspect, the present invention provides a lithium squarate nanosheet, wherein the lithium squarate nanosheet is prepared by the preparation method of the lithium squarate nanosheet as described in the first aspect.

[0021] Preferably, the thickness of the lithium squarate nanosheets is less than 6 nm, preferably 4 to 6 nm, and more preferably 5 nm.

[0022] In a third aspect, the present invention provides a use of the lithium squarate nanosheets as described in the second aspect as a positive electrode lithium supplement material for a lithium battery.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The ultrathin lithium squarate nanosheets prepared by the present invention can be used as a lithium supplement for the positive electrode of lithium batteries. The lithium supplement is efficient, non-toxic, has a simple preparation process, high stability, is easy to operate, and has low cost. It has broad application prospects and potential industrial value, and can be extended to the synthesis of other materials.

[0025] (2) The present invention utilizes the extra lithium ions provided by the lithium ion nanosheets during the charging process of the lithium battery to compensate for the irreversible lithium ion consumption caused by side reactions or interface formation in the battery system, so as to increase the actual capacity of the entire battery and effectively improve the cycle life and energy density of the lithium ion battery; based on the influence on the electrochemical performance of the battery, the morphology and structure of the lithium supplement additive are selectively regulated and designed, so that the obtained positive electrode material can improve the cycle life and energy density while meeting the conventional performance of lithium ion batteries.

[0026] (3) The present invention controls the preparation method of lithium squarate, which can ensure the stability of the obtained squarate on the one hand, and control the morphology of the lithium squarate on the other hand, so that the obtained lithium squarate has better electrochemical properties as a lithium supplement additive. In addition, it can avoid the obtained squarate containing crystal water, avoid the problem of difficult removal of crystal water, and will not affect the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 1 is an X-ray diffraction (XRD) diagram of the lithium squarate nanosheet provided in Example 1 and the lithium squarate sheet provided in Comparative Example 1.

[0029] Figure 2 This is a scanning electron microscope (SEM) image of the lithium squarate nanosheet provided in Example 1.

[0030] Figure 3 This is a scanning electron microscope (SEM) image of the lithium squarate sheet provided in Comparative Example 1.

[0031] Figure 4 This is a scanning electron microscope (SEM) image of the lithium squarate sheet provided in Comparative Example 2.

[0032] Figure 5 This is an atomic force microscope (AFM) image of the lithium squarate nanosheet provided in Example 1 and a corresponding height profile image.

[0033] Figure 6 It is a nitrogen (N2) adsorption-desorption isotherm curve diagram and specific surface area of ​​the lithium squarate nanosheets provided in Example 1 and the comparative example 1 and lithium squarate sheets.

[0034] Figure 7 1 is an X-ray diffraction (XRD) diagram of the newly prepared squarate lithium nanosheets provided in Example 1 and the squarate lithium nanosheets after being stored in air for 180 days.

[0035] Figure 8 It is the first charging curve of the squarate lithium nanosheet provided in Example 1 and the squarate lithium sheet of Comparative Example 1. DETAILED DESCRIPTION

[0036] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0037] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In a first aspect, the present invention provides a method for preparing a lithium squarate nanosheet, the method for preparing the lithium squarate nanosheet comprising:

[0040] Squarate, a lithium source and a template regulator are mixed in alcohol and then subjected to a solvent thermal reaction to obtain squarate lithium nanosheets.

[0041] In the present invention, ultrathin squarate lithium nanosheets are successfully synthesized by a solvothermal method using squarate and lithium source as raw materials and alcohol as medium with the assistance of a template regulator. The solvothermal synthesis method can prepare ultrathin squarate lithium nanosheets with a certain thickness and high specific surface area at a relatively low cost by controlling the reaction conditions. If the ultrathin squarate lithium nanosheets prepared by the solvothermal synthesis method can successfully overcome the existing challenges and achieve large-scale production, they have the potential to become one of the key innovations to promote the advancement of lithium-ion battery technology.

[0042] As an optional embodiment, the molar ratio of the squaric acid to the lithium in the lithium source is 1:(2.0-2.4), for example, it can be 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, etc.

[0043] It should be noted that the present invention controls the molar ratio of squaric acid to lithium source to obtain ultrathin squaric acid lithium nanosheets. If the molar ratio is too low, the size of the obtained material will be uneven, and if the molar ratio is too high, the lithium salt will be excessive and impurities will be present in the product.

[0044] As an optional embodiment, the lithium source includes any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium bicarbonate or lithium acetate, or a combination of at least two thereof.

[0045] As an optional embodiment, the added amount of the template regulator accounts for 0.1-5.0% of the total mass of the square acid and the lithium source, for example, it can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc.

[0046] It should be noted that the present invention controls the addition amount of the template regulator within 0.1-5.0%, based on which ultrathin lithium squarate nanosheets are obtained. If the concentration is too low, the size of the obtained material is uneven, and if the concentration is too high, the product material agglomerates.

[0047] As an optional embodiment, the template regulator includes any one or a combination of at least two of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecylsulfonate, oleic acid or polyethylene glycol.

[0048] As an optional embodiment, the amount of the alcohol added is 1 to 5 times the total mass of the squaric acid and the lithium source, for example, it can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 times, etc.

[0049] As an optional embodiment, the alcohol is selected from any one or a combination of at least two of ethanol, ethylene glycol, glycerol, pentaerythritol, trimethylolethane, xylitol or sorbitol.

[0050] It should be noted that, since the product lithium quarate is soluble in water but insoluble in organic alcohol, alcohol is selected as the medium in the synthesis process. First, the polarity of alcohol is relatively weak, which helps to reduce the interaction between the solvent and the layered material, thereby facilitating the stripping of the layered structure and forming an ultra-thin two-dimensional nanosheet. Secondly, the surface energy of alcohol may be more compatible with the surface energy of certain layered materials, which helps to maintain the stability of the nanosheet during the stripping process. Finally, in an alcohol solvent, the template regulator can form ordered aggregates such as micelles, reverse micelles, and microemulsions, which can be used as microreactors or templates to achieve regulation of the morphology of nanomaterials. In this case, the template regulator can reduce the energy loss during the stripping process and stabilize the stripped thin sheet, thereby making the stripping process more effective. In summary, the present invention regulates the crystalline phase, morphology, and particle size distribution of the material through the specific chemical action of the alcohol solvent, thereby optimizing the electrochemical activity and stability of the material.

[0051] As an optional embodiment, the mixing is carried out under stirring conditions, and the stirring speed is 200-1500rpm, for example, it can be 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, 1500rpm, etc.

[0052] As an optional embodiment, the mixing is carried out under stirring conditions, and the stirring temperature is 5 to 80°C, for example, it can be 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0053] As an optional embodiment, the mixing is carried out under stirring conditions, and the stirring time is 0.5 to 2 hours, for example, it can be 0.5 hours, 0.6 hours, 0.8 hours, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, etc.

[0054] As an optional embodiment, the temperature of the solvothermal reaction is 100-160°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, etc.

[0055] As an optional embodiment, the solvent thermal reaction time is 4 to 12 hours, for example, it can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.

[0056] It should be noted that the morphology and properties of nanomaterials can be effectively regulated by precisely controlling the conditions of the hydrothermal reaction. The present invention helps to suppress stacking by controlling the appropriate extension of the hydrothermal time, and the material grows more obviously along the two-dimensional plane direction, which is conducive to the preparation of ultra-thin nanosheets.

[0057] It can be understood that the above embodiments of the present application use squaric acid and lithium source as raw materials, with the assistance of a template regulator and alcohol as a medium, under hydrothermal conditions, so that the product lithium squarate grows in a two-dimensional direction, and finally forms an ultra-thin two-dimensional nanosheet structure.

[0058] It should be noted that the preparation method of the present invention is not limited to the preparation of lithium squarate nanosheets, but can also be applied to the preparation of other lithium sodium salt nanosheets. For example, the corresponding sodium squarate, lithium oxalate, and sodium oxalate nanosheets can be obtained by reacting squaric acid, oxalic acid, etc. with lithium and sodium salts.

[0059] In a second aspect, the present invention provides a lithium squarate nanosheet (the chemical formula of the lithium squarate is Li2C4O4), and the lithium squarate nanosheet is prepared by the preparation method of the lithium squarate nanosheet as described in the first aspect.

[0060] In the present invention, ultrathin lithium squarate nanosheets with a certain thickness and a high specific surface area are prepared. Ultrathin lithium supplements have unique advantages. They are usually made of extremely thin materials with a thickness ranging from only a few nanometers to tens of nanometers. This ultrathin structural design allows lithium ions to diffuse faster in the electrode material, thereby significantly improving the charge and discharge rate of the battery. In addition, ultrathin lithium supplements also help to improve the energy density of the battery because they can provide more lithium ions to participate in the charge and discharge reaction without increasing the volume of the battery.

[0061] More importantly, due to the ultra-thin nature of the squarate lithium nanosheets, their volume changes during the charge and discharge process are small, which helps to reduce fatigue and degradation of battery materials and extend the service life of the battery. At the same time, the preparation process of the squarate lithium nanosheets described in the present invention is more sophisticated, and the composition and structure of the material can be more accurately controlled, thereby optimizing the performance of the battery. This method can not only improve the conductivity of the material and the diffusion rate of lithium ions, but also maintain the structural stability of the material, thereby improving the charge and discharge rate and cycle stability of the battery.

[0062] As an optional implementation, the ultra-thin lithium squarate nanosheet has a sheet-like structure.

[0063] As an optional embodiment, the thickness of the lithium squarate nanosheets is 4 to 6 nm, for example, 4 nm, 4.2 nm, 4.4 nm, 4.6 nm, 4.8 nm, 5 nm, 5.2 nm, 5.4 nm, 5.6 nm, 5.8 nm, 6 nm, etc., preferably 5 nm.

[0064] As an optional embodiment, the specific surface area of ​​the lithium squarate nanosheets is 80 to 85 m 2 / g, for example, it can be 80m 2 / g, 80.5m 2 / g, 81m 2 / g, 81.5m 2 / g, 82m 2 / g, 82.5m 2 / g, 83m 2 / g, 83.5m 2 / g, 84m 2 / g, 84.5m 2 / g, 85m 2 / g, etc.

[0065] It should be noted that the method for preparing ultrathin squarate lithium nanosheets provided by the present invention through the above-mentioned embodiment uses squarate and lithium salt as precursors, alcohol as a medium, and with the assistance of a template regulator, synthesizes squarate lithium under hydrothermal conditions, so that the prepared squarate lithium nanosheets can exist stably, have an ultrathin nanosheet morphology, and a microscopic thickness of 5nm, further increasing the specific surface area of ​​the material, providing more contact area and active sites, and having good stability, and also provides a new idea for the synthesis of similar lithium and sodium supplements.

[0066] In a third aspect, the present invention provides a use of the lithium squarate nanosheets as described in the second aspect as a positive electrode lithium supplement material for a lithium battery.

[0067] It should be noted that the ultra-thin squarate lithium nanosheets provided by the present invention through the above-mentioned embodiment can be obtained under different concentrations and hydrothermal conditions, and the reaction time is not long, and a stable existence of squarate lithium can be obtained, batch production can be achieved, the synthesis method is simple, and the operation is convenient. The squarate lithium nanosheets of the present invention are efficient, non-toxic, simple in preparation process, high in stability, easy to operate, low in cost, and have broad application prospects and potential industrial value. The ultra-thin squarate lithium nanosheets provided by the present invention reduce the delithiation potential of the material, improve its gram capacity, play an obvious lithium supplement effect, and can be applied to the positive electrode of lithium ion batteries to supplement lithium, and have a good market prospect.

[0068] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0069] Example 1

[0070] The present embodiment provides a lithium squarate nanosheet, which is prepared by the following steps: adding 0.03 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and 7.4 g of lithium carbonate to a polytetrafluoroethylene liner, stirring and adding 50 mL of ethanol, and then adding 11.4 g of squaric acid, stirring at room temperature and a rotation speed of 300 rpm for 2 hours, putting it into a steel sleeve, heating it at 120° C. in an oven for 4 hours, and after the reaction is completed, naturally cooling it to room temperature, washing it by centrifugation, and drying it in an oven to obtain the lithium squarate nanosheet.

[0071] Example 2

[0072] The present embodiment provides a lithium squarate nanosheet, which is prepared by the following steps: weighing 0.02 g of CTAB and 13.6 g of lithium bicarbonate, adding them to a polytetrafluoroethylene liner, stirring and adding 50 mL of ethylene glycol, and then adding 11.4 g of squaric acid, stirring at 60° C. and 600 rpm for 1 hour, putting it into a steel sleeve, heating it at 140° C. in an oven for 8 hours, and after the reaction is completed, naturally cooling it to room temperature, washing it by centrifugation, and drying it in an oven to obtain the lithium squarate nanosheet.

[0073] Example 3

[0074] The present embodiment provides a lithium squarate nanosheet, which is prepared by the following steps: weighing 0.04 g of oleic acid and 4.8 g of lithium hydroxide, adding them into 100 mL of polytetrafluoroethylene liner, stirring and adding 50 mL of ethylene glycol, and then adding 11.4 g of squaric acid, stirring at 60° C. and 800 rpm for 1 hour, putting it into a steel sleeve, heating it at 120° C. in an oven for 10 hours, and after the reaction is completed, naturally cooling it to room temperature, washing it by centrifugation, and drying it in an oven to obtain the lithium squarate nanosheet.

[0075] Example 4

[0076] This embodiment provides a lithium squarate nanosheet, which is different from Embodiment 1 only in that the molar ratio of squarate to lithium carbonate is 1:1.5, and the other steps are completely consistent with Embodiment 1.

[0077] Example 5

[0078] This embodiment provides a lithium squarate nanosheet, which is different from Embodiment 1 only in that the molar ratio of squarate to lithium carbonate is 1:2.5, and the other steps are completely consistent with Embodiment 1.

[0079] Example 6

[0080] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that the lithium carbonate is replaced with lithium oxide of the same mass, and the other steps are completely consistent with the embodiment 1.

[0081] Example 7

[0082] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that the content of the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) is adjusted to 0.01 g, and the other steps are completely consistent with the embodiment 1.

[0083] Example 8

[0084] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that the content of the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) is adjusted to 1 g, and the other steps are completely consistent with the embodiment 1.

[0085] Example 9

[0086] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) is replaced by polyvinyl pyrrolidone of equal mass, and the other steps are completely consistent with the embodiment 1.

[0087] Example 10

[0088] This embodiment provides a lithium squarate nanosheet, which is different from Embodiment 1 only in that the content of ethanol is reduced to 20 mL, and the other steps are completely consistent with Embodiment 1.

[0089] Embodiment 11

[0090] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that the content of the ethanol is increased to 80 mL, and the other steps are completely consistent with the embodiment 1.

[0091] Example 12

[0092] This embodiment provides a lithium squarate nanosheet, which is different from Embodiment 1 only in that the ethanol is replaced with an equal volume of glycerol, and the other steps are completely consistent with Embodiment 1.

[0093] Example 13

[0094] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that it is heated in an oven at 100° C. for 12 h, and the other steps are completely consistent with the embodiment 1.

[0095] Embodiment 14

[0096] This embodiment provides a lithium squarate nanosheet, which is different from the embodiment 1 only in that it is heated in an oven at 160° C. for 4 h, and the other steps are completely consistent with the embodiment 1.

[0097] Comparative Example 1

[0098] The comparative example provides a lithium squarate tablet, which is prepared by the following steps: 11.4 g of squaric acid and 7.4 g of lithium carbonate are respectively dissolved in 25 mL of deionized water, the squaric acid aqueous solution is slowly added to the lithium carbonate aqueous solution in a 60° C. water bath for several times, and after the squaric acid aqueous solution is completely added, stirring is continued for 2 hours to obtain a lithium squarate solution, and the squaric acid sample is prepared by drying after evaporation, concentration, crystallization and drying.

[0099] Comparative Example 2

[0100] This comparative example provides a lithium squarate tablet, which is different from Example 1 only in that the ethanol is replaced by an equal volume of water, and the other steps are completely consistent with Example 1.

[0101] Comparative Example 3

[0102] This comparative example provides a lithium squarate sheet, which is different from Example 1 only in that the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) is no longer added, and the other steps are completely consistent with Example 1.

[0103] Test Example 1

[0104] Test samples: the squarate lithium nanosheets provided in Examples 1 to 14 and the squarate lithium sheets provided in Comparative Examples 1 to 3.

[0105] Test items: X-ray diffraction, scanning electron microscopy and atomic force microscopy.

[0106] The test results are shown in Table 1 and below. Figure 1 to Figure 7 As shown:

[0107] Table 1

[0108]

[0109]

[0110] As shown in Table 1, the thickness of the lithium squarate nanosheets prepared by the preparation methods provided in Examples 1 to 3 of the present invention is 5.0 to 6.0 nm, and the specific surface area of ​​the lithium squarate nanosheets is 81.5 to 85.0 m 2 / g. It is thus shown that the method for preparing ultrathin squarate lithium nanosheets provided by the above embodiment of the present invention uses squarate and lithium salt as precursors, alcohol as a medium, and with the assistance of a template regulator, synthesizes squarate lithium under hydrothermal conditions, so that the prepared squarate lithium nanosheets can exist stably, have an ultrathin nanosheet morphology, and a microscopic thickness of 5nm, further increasing the specific surface area of ​​the material, providing more contact areas and active sites, and having good stability.

[0111] Figure 1 The X-ray diffraction (XRD) diagram of the lithium squarate nanosheets provided in Example 1 and the lithium squarate sheets provided in Comparative Example 1 is shown in FIG. Figure 1 In the comparison, it can be found that the prepared samples are all pure phases, and the average lithium squarate standard card is consistent, but the small size of the nanosheets and the preferential orientation of the sample crystal phase cause the diffraction peaks to produce more burrs.

[0112] Figure 2 is a scanning electron microscope (SEM) image of the lithium squarate nanosheet provided in Example 1; Figure 3is a scanning electron microscope (SEM) image of the lithium squarate sheet provided in Comparative Example 1; Figure 4 This is a scanning electron microscope (SEM) image of a lithium squarate sheet provided in Comparative Example 2. First, Figure 2 and Figure 3 It can be seen from the comparison that under the same multiple conditions, the comparative example 1 presents a layered bulk structure, while the lithium squarate nanosheets prepared in Example 1 are separated thin sheet structures. Figure 2 and Figure 4 It can be seen from the comparison that since the product lithium quartz itself is easily soluble in water, it cannot grow in a directional manner under the action of the template regulator, and thus cannot form nanosheets. The final form is a recrystallized thick sheet after drying.

[0113] Figure 5 1 is an atomic force microscope (AFM) image of the lithium squarate nanosheet provided in Example 1 and a corresponding height profile image. Figure 5 It can be seen that the average thickness of the lithium squarate nanosheets provided in Example 1 is 5 nm.

[0114] Figure 6 The isotherm curves of nitrogen (N2) adsorption and desorption of the lithium squarate nanosheets provided in Example 1 and the lithium squarate nanosheets in Comparative Example 1 and their specific surface areas. It can be seen from the figure that the specific surface area of ​​the lithium squarate nanosheets prepared in Example 1 is 82.9 m 2 / g, while the specific surface area of ​​the lithium squarate product prepared in the comparative example is only 10.7m 2 / g, it is obvious that the specific surface area of ​​the lithium squarate nanosheets prepared in Example 1 is 7.7 times that of the comparative example, which fully demonstrates that the preparation method of the present invention further increases the specific surface area of ​​the material and provides more contact area and active sites.

[0115] Figure 7 1 is an X-ray diffraction (XRD) diagram of the newly prepared squarate lithium nanosheets provided in Example 1 and the squarate lithium nanosheets stored in air for 180 days. Figure 7 It can be found that there is no difference in XRD between the lithium squarate nanosheets exposed to air for a long time and the newly prepared lithium squarate nanosheets, which further shows the excellent air stability of the lithium squarate nanosheets prepared by the method of the present invention.

[0116] Test Example 2

[0117] Test samples: the squarate lithium nanosheets provided in Examples 1 to 14 and the squarate lithium sheets provided in Comparative Examples 1 to 3.

[0118] Test item: Lithium squarate battery buckling test.

[0119] Test method:

[0120] The quartzite material to be tested (quartzite nanosheets, quartzite comparative example), binder (PVDF), and conductive agent are mixed in a mass ratio of 80:10:10, and dispersant N-methylpyrrolidone (NMP) is added to make a slurry, which is evenly coated on aluminum foil, baked and pressed into sheets, and then punched, and dried at 80°C in a drying oven for 12 hours before use. A metal lithium sheet is used as the counter electrode, a 1mol / L LiPF6 electrolyte is used, and the solvent is a three-component mixed solvent, i.e., a mixture of EC:DMC:EMC with a volume ratio of 1:1:1. Celgard 2400 microporous polypropylene membrane is used as a diaphragm, and a CR2032 button cell is assembled in an argon glove box. The charge and discharge test of the button cell is carried out on a blue battery test system, with a charge and discharge voltage of 2.0 to 4.4V, a charge and discharge rate of 0.1C, and the first charge capacity is tested.

[0121] The test results are shown in Table 2 and below. Figure 8 As shown:

[0122] Table 2

[0123]

[0124]

[0125] As shown in Table 2, the first cycle charging capacity of the half-cell prepared by using the lithium squarate nanosheets provided in Examples 1 to 3 of the present invention as the positive electrode lithium supplement material of the lithium battery is 436.5 to 446 mAh / g.

[0126] Obviously, the first cycle charge capacity of the corresponding half-cell of the lithium squarate nanosheets synthesized by the solvothermal method in Examples 1, 2, and 3 of the present invention is much higher than that of Comparative Examples 1 and 2. In addition, Example 1 and Comparative Example 2 show significantly different half-cell performances under the same reaction conditions except for the different solvents (alcohol and water). This may be because the product lithium squarate itself is easily soluble in water and cannot grow in a directional manner under the action of surfactants, thereby failing to form nanosheets, and the final form is a recrystallized thick sheet after drying.

[0127] Test Example 3

[0128] Test samples: the squarate lithium nanosheets provided in Examples 1 to 14 and the squarate lithium sheets provided in Comparative Examples 1 to 3.

[0129] Test item: Lithium-ion battery test.

[0130] Test method:

[0131] The above samples were mixed with lithium iron phosphate positive electrode material, acetylene black conductive agent, and PVDF in a ratio of 5:75:10:10, and then added to NMP to obtain a black viscous slurry. The slurry was applied to aluminum foil and dried to obtain a positive electrode sheet containing lithium quartz. The metal lithium, the diaphragm, and the prepared positive electrode sheet were assembled into a button battery. The button battery model used was CR2032, the diaphragm model was 2500, and the electrolyte was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1). After assembly, the battery was removed from the glove box and left to stand at 30°C for 12 hours before being tested on the Land test system. The charge and discharge voltage was 2.0 to 4.4V, the charge and discharge rate was 0.1C, and the first reversible capacity was tested.

[0132] The test results are shown in Table 3 and Figure 8 As shown:

[0133] Table 3

[0134]

[0135]

[0136] As shown in Table 2, the lithium squarate nanosheets provided in Examples 1 to 3 of the present invention are used as positive electrode lithium replenishment materials for lithium batteries. The first cycle charge capacity of the prepared battery is 200 to 220 mAh / g, the discharge capacity is 150 to 160 mAh / g, the lithium replenishment rate is more than 29%, and the capacity retention rate is more than 95%. The first cycle charge capacity, first cycle discharge capacity, lithium replenishment rate and cycle capacity retention rate of the full battery corresponding to Examples 1, 2 and 3 are all higher than those of Comparative Examples 1 and 2. Therefore, the synthesized ultra-thin two-dimensional lithium squarate nanosheets have high lithium replenishment activity and are a positive electrode lithium replenishment material with broad application prospects.

[0137] Figure 8 The first charging curves of the lithium squarate nanosheets synthesized in Example 1 and its lithium squarate comparative example 1 are shown. The delithiation potential of the lithium squarate comparative example 1 is 4.2V, and the charge specific capacity is 162.5mAh / g. After nano-treatment, the ultra-thin lithium squarate nanosheets significantly improve the electrochemical properties of the material, reduce the delithiation potential to 3.9V, and the charge specific capacity can reach 446.7mAh / g, which is increased by nearly 1.8 times.

[0138] Based on the above experimental examples, the ultra-thin nano-lithium square acid provided by the present invention has a charging capacity close to the theoretical value, a low lithium de-potential, and is compatible with the positive electrode system; when added to the lithium iron phosphate system, it significantly enhances the first cycle charge and discharge efficiency and maintains a high cycle capacity retention rate, has an excellent lithium supplement effect, and ensures the cycle stability of the battery. In addition, the preparation process of the present invention is simple, stable, easy to operate, and low in cost, and has broad application prospects and potential industrial value.

[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing lithium squarate nanosheets, characterized in that: The preparation method of the lithium squarate nanosheets comprises: Squarate, a lithium source and a template regulator are mixed in alcohol and then subjected to a solvent thermal reaction to obtain squarate lithium nanosheets.

2. The method for preparing lithium squarate nanosheets according to claim 1, characterized in that: The molar ratio of the squaric acid to the lithium in the lithium source is 1:(2.0-2.4).

3. The method for preparing lithium squarate nanosheets according to claim 1 or 2, characterized in that: The lithium source includes any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium bicarbonate or lithium acetate, or a combination of at least two thereof.

4. The method for preparing lithium squarate nanosheets according to claim 1, characterized in that: The added amount of the template regulator accounts for 0.1-5.0% of the total mass of the squaric acid and the lithium source.

5. The method for preparing lithium squarate nanosheets according to claim 1 or 4, characterized in that: The template regulator includes any one of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecylsulfonate, oleic acid or polyethylene glycol, or a combination of at least two thereof.

6. The method for preparing lithium squarate nanosheets according to claim 1, characterized in that: The added amount of the alcohol is 1 to 5 times the total mass of the squaric acid and the lithium source.

7. The method for preparing lithium squarate nanosheets according to claim 1, characterized in that: The alcohol is selected from any one or a combination of at least two of ethanol, ethylene glycol, glycerol, pentaerythritol, trimethylolethane, xylitol or sorbitol.

8. The method for preparing lithium squarate nanosheets according to claim 1, characterized in that: The mixing is carried out under stirring conditions, the stirring speed is 200 to 1500 rpm, the stirring temperature is 5 to 80° C., and the stirring time is 0.5 to 2 h; Preferably, the temperature of the solvent thermal reaction is 100 to 160° C., and the time of the solvent thermal reaction is 4 to 12 hours.

9. A lithium squarate nanosheet, characterized in that: The squarate lithium nanosheets are prepared by the preparation method of squarate lithium nanosheets according to any one of claims 1 to 8; And / or, the thickness of the lithium squarate nanosheets is 4 to 6 nm; And / or, the specific surface area of ​​the lithium squarate nanosheets is 80 to 85 m 2 / g.

10. Use of the squarate lithium nanosheet according to claim 9 as a positive electrode lithium supplement material for lithium batteries.

Citation Information

Patent Citations

  • Lithium squarate and preparation method and application thereof

    CN113443973A

  • Cathode and cathode slurry for secondary battery

    US20230073006A1